Edukasi Pencegahan Kenakalan Remaja di Lingkungan Sekolah : Pengabdian - Rahmadi Ali; Rosmilan Pulungan; M. Faisal Husna; Ikhwan Nul Hakim; Zaiyyidil Munawar Arsyad; Inka Sari Pulungan; Nabila Sari; Raudatul Jannah; Savira Putri Hidayat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service aims to provide education on preventing juvenile delinquency in the school environment, specifically in class XI 2 of SMAN 13 Medan, North Sumatra, Indonesia. From the community service activities where the implementation of the MKWK program class of 2025 Al-Washliyah Muslim Nusantara University, Medan, North Sumatra, Indonesia. The conclusions obtained include: through this educational activity it is hoped that it can provide insight into the impact of juvenile delinquency. With this education it is hoped that delinquency among teenagers will be reduced and provide them with insight into the impacts that will occur from each juvenile delinquency they commit, so that it can create a safe school environment to encourage better future planning. This activity was carried out through counseling, simulation of cases/types of juvenile delinquency, and interactive discussions between us UMN students as resource persons and students. In addition, students were given a complete ppt about juvenile delinquency as well as its types and solutions. Students were also given time to write and tell what they experienced during school. The resource person also provided efforts and solutions in preventing juvenile delinquency and gave a small prize to students who had written and told their story in front of the class. Obstacles that arose included the difficulty of coordinating meeting times with the administration administrators in submitting correspondence.